Gene Networks Underlying the Resistance of Bifidobacterium longum to Inflammatory Factors - Veselovsky, Vladimir A.; Dyachkova, Marina S.; Menyaylo, Egor A.; Polyaeva, Polina S.; Olekhnovich, Evgenii I.; Shitikov, Egor A.; Bespiatykh, Dmitry A.; Semashko, Tatiana A.; Kasianov, Artem S.; Ilina, Elena N.; Danilenko, Valeriy N.; Klimina, Ksenia M. (Frontiers in Immunology, 2020)
As permanent residents of the normal gut microbiota, bifidobacteria have evolved to adapt to the host’s immune response whose priority is to eliminate pathogenic agents. The mechanisms that ensure the survival of commensals during inflammation and maintain the stability of the core component of the normal gut microbiota in such conditions remain poorly understood. We propose a new in vitro approach to study the mechanisms of resistance to immune response factors based on high-performance sequencing followed by transcriptome analysis. This approach allowed us to detect differentially expressed genes associated with inflammation. In this study, we demonstrated that the presence of the pro-inflammatory cytokines IL-6 and TNFα to the growth medium of the B. longum GT15 strain changes the latter’s growth rate insignificantly while affecting the expression of certain genes. We identified these genes and performed a COG and a KEGG pathway enrichment analysis. Using phylogenetic profiling we predicted the operons of genes whose expression was triggered by the cytokines TNFα and IL-6 in vitro. By mapping the transcription start points, we experimentally validated the predicted operons. Thus, in this study, we predicted the genes involved in a putative signaling pathway underlying the mechanisms of resistance to inflammatory factors in bifidobacteria. Since bifidobacteria are a major component of the human intestinal microbiota exhibiting pronounced anti-inflammatory properties, this study is of great practical and scientific relevance.